2017
DOI: 10.1007/s00467-017-3637-0
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in pediatric kidney transplant recipients: solutions for the system

Abstract: Non-adherence remains a significant problem among pediatric (and adult) renal transplant recipients. Non-adherence among solid organ transplant recipients results in US$15-100 million annual costs. Estimates of non-adherence range from 30 to 70% among pediatric patients. Research demonstrates that a 10% decrement in adherence is associated with 8% higher hazard of graft failure and mortality. Focus has begun to shift from patient factors that impact adherence to the contributing healthcare and systems factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 121 publications
0
43
0
1
Order By: Relevance
“…This review synthesized the current literature to identify psychosocial predictors of medication non‐adherence among pediatric transplant recipients and their families. Medication non‐adherence in pediatric organ transplantation is a multifaceted health behavior which can be challenging for families caring for a child with a transplanted organ and for healthcare professionals working to promote adherence . Results from the review emphasize the importance of considering psychosocial issues with the child, adolescent, parent or caregiver, and the larger family environment when assessing for post‐transplant medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review synthesized the current literature to identify psychosocial predictors of medication non‐adherence among pediatric transplant recipients and their families. Medication non‐adherence in pediatric organ transplantation is a multifaceted health behavior which can be challenging for families caring for a child with a transplanted organ and for healthcare professionals working to promote adherence . Results from the review emphasize the importance of considering psychosocial issues with the child, adolescent, parent or caregiver, and the larger family environment when assessing for post‐transplant medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Medication non-adherence in pediatric organ transplantation is a multifaceted health behavior which can be challenging for families caring for a child with a transplanted organ and for healthcare professionals working to promote adherence. 94 Results from the review emphasize the importance of considering psychosocial issues with the child, adolescent, parent or caregiver, and the larger family environment when assessing for post-transplant medication adherence. The varying results of the current literature along with the content and methodological gaps that remain in this body of knowledge make it essential for additional research in this area to occur.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…11,22,23 It is also known that socioeconomic conditions, family support, and functioning are major contributors to nonadherence. [24][25][26] Our study has some strengths and limitations. The Renal Epidemiology and Information Network registry is a comprehensive and validated nationwide renal registry that includes all pediatric and adult kidney transplant recipients in France.…”
Section: Discussionmentioning
confidence: 99%
“…Also, adolescents and young adults are typically less adherent to immunosuppressive medication than elderly transplant recipients,8,9 thus increasing the risk of graft rejection or loss 2,8. Based on previous research, the highest allograft rejection rate has been observed in 16- to 21-year-old patients 2,10. Also, the worst clinical outcomes of kidney transplantation are observed in adolescent and young adult transplant recipients as compared to other age groups 11.…”
Section: Introductionmentioning
confidence: 99%